Shifting the Emphasis from Teaching to Learning: Process-Based Assessment in Nurse Education - Bergström, Peter (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Shifting from an emphasis on teaching to learning is a complex task for both teachers and students. This paper reports on a qualitative study of teachers in a nurse specialist education programme meeting this shift in a distance education course. The study aimed to gain a better understanding of the teacher-student relationship by addressing research questions in relation to the students’ role, the learning process, and the assessment process. A didactical design comprising three phases focusing on distinct learning outcomes for the course was adopted. Data were collected through in-depth interviews with teachers and were analysed using inductive thematic analysis. The results indicate a shift towards a problematising and holistic approach to teaching, learning, and assessment. This shift highlighted a teacher-student relationship with a shared responsibility in the orchestration of the learning experience. The overall picture outlines a distance education experience of process-based assessment characterised by the imposition of teachers’ rules and a lack of creativity due to the limited role of ICT merely as a container of content.